Improving electrochemical active area of MoS2 via attached on 3D-ordered structures for hydrogen evolution reaction. (25th October 2019) - Kim, Kisun; Tiwari, Anand P.; Hyun, Gayea; Novak, Travis G.; Jeon, Seokwoo
Abstract: To date, researchers have revealed that the electrocatalytic activity of 2-dimensional (2D) layered transition metal dichalcogenides (TMDCs) such as MoS2 can be improved by making free standing vertical structures to expose edge sites for efficient water splitting. However, poor electrical conductivity and structural instability restrict the practical application of vertical structures for efficient electrocatalytic activities. Here, a homogeneously attached MoS2 structure on well-ordered 3-dimensional nickel (3D-Ni) is reported for efficient hydrogen evolution reaction (HER). This homogeneously attached structure of MoS2 leads to abundant active sites and well-ordered 3D-Ni structures, solving the conductivity issue of MoS2 and ensuring the structural stability during electrocatalytic processes. By controlling the amount of MoS2 on the 3D-Ni, it is found that the electrochemical active area (ECSA) is increased by 5 times (50 cm 2 of active sites) compared to normal MoS2 grown on 2D-Ni (9 cm 2 of active sites). It is also found that the charge transfer resistance (Rct ) of attached MoS2 structures on 3D-Ni (1 Ω) is 16 times lower than MoS2 grown on 2D-Ni (16 Ω). In addition, the proposed attached structure of MoS2 is stable in acidic electrolytes for continuous electrocatalytic activity and can be mass producible for practical applications. Graphical abstract: Image 1 Highlights: A well-ordered 3-dimensional metal (3D-Ni) nanostructures is developed. 2D-MoS2 sheets are homogeneously grown on the 3D-Ni by solvothermal method. Homogeneously attached 2D-MoS2 on 3D-Ni abundant active sites for hydrogen evolution. Well-ordered 3D-Ni ensures stability and high electrochemical conductivity. The 2D/3D structure combo can be used in other electrochemical TMDC applications.